Defeitos dos tungstatos MWO4 (M = Co, Mn e Cu) por simulação atomística - Santos, Aleff de Jesus (2022)
Making use of the static computational modeling method to study structural and intrinsic and extrinsic defects in MWO4, M = Co, Mn and Cu. Potential parameters that reproduce the structural and physical properties of the 3 tungstates, in addition to the precursor oxides related to the materials studied, were modeled. Next, the solution energies for the intrinsic defects were calculated, and we observed that those involving oxygen vacancy have the lowest solution energy. Finally, defects arising from the insertion of divalent and trivalent ions into the tungstate lattice were studied. All calculations were done using the GULP computational package. From the data obtained from the simulations, it is obtained that the most likely defect is when the dopant replaces the divalent ion site M, with charge compensation mechanism by self-compensation for divalent dopants and oxygen interstitial for trivalent dopants.